2023
DOI: 10.3390/foods12122344
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Microwave Treatments Combined with Hot-Air Drying on Phytochemical Profiles and Antioxidant Activities in Lily Bulbs (Lilium lancifolium)

Abstract: Lily bulbs (Lilium lancifolium Thunb.) are rich in phytochemicals and have many potential biological activities which could be deep-processed for food or medicine purposes. This study investigated the effects of microwaves combined with hot-air drying on phytochemical profiles and antioxidant activities in lily bulbs. The results showed that six characteristic phytochemicals were identified in lily bulbs. They also showed that with an increase in microwave power and treatment time, regaloside A, regaloside B, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…It was revealed that the drying time of fruits in the drying process with light emitting diodes (LEDs) was shorter than convective dryers and the drying time decreased as the LED color temperature increased [ 23 , 24 ]. In addition to these methods, hybrid drying studies have been carried out recently, combining drying methods to make food drying faster and more economical [ 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was revealed that the drying time of fruits in the drying process with light emitting diodes (LEDs) was shorter than convective dryers and the drying time decreased as the LED color temperature increased [ 23 , 24 ]. In addition to these methods, hybrid drying studies have been carried out recently, combining drying methods to make food drying faster and more economical [ 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The high polysaccharide content of the bulb makes it the only type of sweet lily that is edible. The bulbs also contain starch, protein, and dietary fiber, making them a medicinal and edible plant in China [2]. Lanzhou lily is a traditional medicinal plant and a bulb plant consumed by the public, with functions that include clearing heat and toxins, nourishing the lungs, fighting cancer, and enhancing human immunity [3].…”
Section: Introductionmentioning
confidence: 99%